Transplanter for plant seedlings. - Yahya, Azmi; El Pebrian, Darius (2011)

(untitled)
Seedling Transplanter Ver-1 is used with a 4-wheel drive tractor having at least 63.4kW for field transplanting of oil palm seedlings or any tree crop seedlings. The design configuration of this transplanter is made up of the main chassis seedling bin, planting assembly, operator compartment and associated hydraulic system. Two operators are required for the transplanting operation; a driver for the tractor and an operator for the transplanter. The driver drives the tractor-transplanter in the field while the operator on the transplanter operates the hydraulic contol system to conduct all the operational activities.